Ultrasonic study of CuxAg1-xInTe2 bulk material - GAAFAR, Mohamed El Sayed; EL-SAYAD, El Sayed Abd El-Halim; MARZOUK, Samir Yousuf (Archives of Acoustics, 2008)
Longitudinal and shear ultrasonic wave velocities were measured in the quaternary compounds CuxAg1-xInTe2 (0[ampersand]le;x[ampersand]le;1) using pulse echo technique. Measurements were carried out at 4 MHz frequency and at room temperature. Elastic moduli and acoustic impedance have been calculated. Results indicated that these parameters are influenced by the increased addition of copper from x=0 to[ampersand]nbsop;1.